Supporting women with learning disabilities in infant feeding decisions: A scoping review - Clare Johnson; Emma Douglass; Geraldine Lucas; Sally Dowling (Wiley, 2022)
Abstract Mothers with learning disabilities face many challenges during the perinatal period including preparing for and establishing infant feeding. Evidence shows that women with learning disabilities are less likely to breastfeed than other mothers. A scoping review was undertaken using Arksey and O'Malley's methodology to understand what is known about how women with learning disabilities can be supported to make infant feeding decisions, particularly in relation to the use of appropriate and accessible images. An additional aim was to understand what further research is needed to achieve sustainable improvements to policy and practice in this area. A comprehensive search of fourteen electronic databases was undertaken to look for both published and grey literature. Initial searches, after removal of duplicates, resulted in 467 primary research articles plus 22 items of grey literature. Following a systematic process, three published papers and six items of grey literature were identified which met inclusion and exclusion criteria, five of which were resources. Little is known about the acceptability of existing resources, specifically in relation to the use of visual images. A synthesis of the grey literature and a thematic analysis of published literature was conducted and confirmed that women with learning disabilities need tailored support with infant feeding, including accessible resources and that there is a need for more in‐depth research in this area. There is a high level of agreement about the importance of using easily read visual images within these resources, but little evaluation of the types of imagery used or their aesthetic histories.